Heavy Metals in Tissues of Blue Crabs Callinectes danae from a Subtropical Protected Estuary Influenced by Mining Residues - Bordon, Isabella C. [UNESP]; Joviano, Willian Reina; de Medeiros, Aline Maria Zigiotto; de Campos, Bruno Galvão [UNESP]; Araujo, Giuliana Seraphim de [UNESP]; Gusso-Choueri, Paloma Kachel [UNESP]; Preto, Mayra de Freitas [UNESP]; Favaro, Deborah Inês Teixeira; Abessa, Denis Moledo de Souza [UNESP] (Springer Nature, 2020)
This short note aims to report in detail a preliminary assessment of the concentrations of Cd, Hg and Pb in tissues of blue crabs Callinectes danae collected from the Cananéia-Iguape-Peruíbe estuarine complex (CIP), in the South of São Paulo State coast, Brazil. In October 2014, blue crabs were collected from CIP. Tissues were removed by dissection and metal determination was performed by GF-AAS and CV-AAS. According to statistical analysis, Pb and Cd concentrations in gills were significantly higher than those found in muscles and hepatopancreas, respectively. There were no significant differences in Hg concentrations between samples. Cd, Hg and Pb concentrations in gills and hepatopancreas were lower than those reported in a previous study performed at CIP. However, Cd concentration in hepatopancreas was higher than the Brazilian limit for consumption and new efforts to monitor Cd concentrations in C. danae tissues must be performed.
Keywords: Blue crab; Callinectes danae; CIP; GF-AAS; Heavy metal